The IMEx coronavirus interactome: an evolving map of Coronaviridae–host molecular interactions. (18th November 2020) - Perfetto, L; Pastrello, C; del-Toro, N; Duesbury, M; Iannuccelli, M; Kotlyar, M; Licata, L; Meldal, B; Panneerselvam, K; Panni, S; Rahimzadeh, N; Ricard-Blum, S; et al.
Abstract: The current coronavirus disease of 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus (SARS-CoV)-2, has spurred a wave of research of nearly unprecedented scale. Among the different strategies that are being used to understand the disease and develop effective treatments, the study of physical molecular interactions can provide fine-grained resolution of the mechanisms behind the virus biology and the human organism response. We present a curated dataset of physical molecular interactions focused on proteins from SARS-CoV-2, SARS-CoV-1 and other members of the Coronaviridae family that has been manually extracted by International Molecular Exchange (IMEx) Consortium curators. Currently, the dataset comprises over 4400 binarized interactions extracted from 151 publications. The dataset can be accessed in the standard formats recommended by the Proteomics Standards Initiative (HUPO-PSI) at the IntAct database website (https://www.ebi.ac.uk/intact ) and will be continuously updated as research on COVID-19 progresses.